Synthesis of new mixed metal oxide RuNi2O4 phase decorated on reduced graphene oxide for supercapacitor applications. (20th August 2022) - Bera, Sumanta; Miah, Milon; Mondal, Tapas Kumar; Debnath, Anup; Saha, Shyamal Kumar
Highlights: New mixed metal RuNi2 O4 nano particle decorated rGO (RuNi2 O4 /rGO) has been synthesized. RuNi2 O4 /rGO offers high specific capacitance of 792 Fg −1 . RuNi2 O4 /rGO retains 93% of initial specific capacitance after 10, 000 cycles. Abstract: Design and fabrication of high performance energy storage devices using different mixed metal oxides decorated on conducting 2D surfaces are being investigated intensively now a days. In the present work, we have explored to synthesize a new mixed metal oxide (RuNi2 O4 ) containing Ru and Ni and decorate the nanoparticles of these mixed metal oxides on highly conducting 2D reduced graphene oxide (rGO) surfaces to prepare efficient electrodes for high performance supercapacitors. The microstructure and compositional analyses of the composite structure are carried out by powder X-ray diffraction (XRD), transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). The XRD data have been analysed by Rietveld refinement. The electrochemical performance of the device has been investigated via galvanostatic charging-discharging (GCD), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analyses. It is seen that RuNi2 O4 /rGO composite shows a very high specific capacitance of 792 Fg −1 compared to the values of rGO and pristine RuNi2 O4 as 235 and 367 Fg −1, respectively. Due to the combined effect of the electric double layer contribution of rGO and the faradaic contribution of RuNi2 O4, RuNi2 O4 /rGO composite results in this high value of specific capacitance in the composite structure.